2018
DOI: 10.1108/lodj-11-2017-0350
|View full text |Cite
|
Sign up to set email alerts
|

National citizenship as a mediator of organizational innovation

Abstract: Purpose The purpose of this paper is to report an initial investigation into the role of national citizenship status in relation to leadership and organizational innovation in the context of the United Arab Emirates, an Arabian Gulf country with a workforce in which migrants far outweigh the number of locals. Design/methodology/approach The authors use grounded theory methodology to gather initial data and reveal potentially appropriate theory for further research into the role of national citizenship as it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In other words, these leaders' capital is low given their expatriate status and limited job security, and a consequence of this is their preference for adhering closely to organizational schemata and eschewal of possible innovativeness. This hypothesis is borne out by a UAE study that found that citizen leaders display a far greater tendency to deviate from established organizational procedures than expatriate leaders (Goby and Alhadhrami, 2018). Divergence and innovation go hand in hand (Anderson et al, 2014), but, as Chen et al (2005) demonstrate, innovation can give rise to conflict, clearly something that less secure leaders will typically strive to avoid.…”
Section: Impact Of Status On Leader Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, these leaders' capital is low given their expatriate status and limited job security, and a consequence of this is their preference for adhering closely to organizational schemata and eschewal of possible innovativeness. This hypothesis is borne out by a UAE study that found that citizen leaders display a far greater tendency to deviate from established organizational procedures than expatriate leaders (Goby and Alhadhrami, 2018). Divergence and innovation go hand in hand (Anderson et al, 2014), but, as Chen et al (2005) demonstrate, innovation can give rise to conflict, clearly something that less secure leaders will typically strive to avoid.…”
Section: Impact Of Status On Leader Behaviormentioning
confidence: 99%
“…Our findings suggest that the lack of national citizenship status may constitute a vital part of an actor's context which affords more limited material for possible divergence and innovation. In the UAE context, the expatriate's status is lower than the citizen's Forstenlechner, 2010, 2012;Goby and Alhadhrami, 2018), and this lower status generates a sense of being marginalized (Walton, et al, 2012). It could be hypothesized that in contexts of escalating professional migration, national citizenship status comes to function in a way similar to how Bourdieu (1997) argues educational qualification does in France, namely, that it may confer an inherent status-enhancing benefit.…”
Section: Impact Of Status On Leader Behaviormentioning
confidence: 99%